Service-oriented architecture : concepts, technology, and design - Erl, Thomas (Upper Saddle River, NJ : Prentice Hall PTR, 2005)
Provides information on how to model and design service-oriented SOA platforms.
Includes index.
osc 29/04/13
Loan
Keywords: Computer architecture; Web services; Service orientation - computer